Analysis of global trends in caesarean section rates using the Robson classification - E. Yu. Lebedenko; A. V. Bespalaya; T. E. Feoktistova; M. A. Rymashevskiy (Медицинский вестник Юга России, 2021)
The rate of Cesarean section (CS) continues to rise and researchers have no clear understanding of the underlying drivers and consequences. Robson’s 10-group classification is based on simple obstetric parameters (parity, prior CS, gestational age, onset of labor, fetal presentation, and a number of fetuses), which allowed the authors to make an effective evaluation of indicators that lead to an increase in the frequency of abdominal delivery. In the context of the global increase in the frequency of abdominal delivery, further modification of the scale will allow the specialists not only to assess the frequency of CS but also to assess the levels of perinatal morbidity and mortality in the groups that make the most significant contribution to the level of CS. Global trends in the commercialization of childbirth require global approaches to reduce the level of abdominal delivery in the population.